Gerakan Menulis Book Chapter (Genbocha): Workshop Penulisan Book Chapter bagi Guru MTSN 9 Jombang - Islam, Aang Fatihul; Sholikhah, Masriatus; Ni’amah, Afi (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Writing scientific papers is an essential component in the evaluation of e-performance; however, many teachers have not yet been able to achieve this due to a lack of knowledge about writing and publishing scientific work. The community service activity aims to enhance the academic literacy capacity of teachers at MTsN 9 Jombang through the GENBOCHA Workshop (Gerakan Menulis Book Chapter or the Book Chapter Writing Movement). The approach used is Community-Based Participatory Research (CBPR), which positions teachers as active partners in the planning, implementation, and evaluation stages of the program. The activity was carried out through a series of training sessions, participatory discussions, and intensive mentoring. The results showed a significant improvement in participants' understanding and skills related to the structure and techniques of book chapter writing. This initiative also fostered the development of a sustainable literacy community within the madrasah.